Cathode–Sulfide Solid Electrolyte Interfacial Instability: Challenges and Solutions - Brahmbhatt, Teerth; Yang, Guang; Self, Ethan; Nanda, Jagjit (Frontiers in Energy Research, 2020)
All-solid-state batteries (ASSBs) are a candidate for next-generation energy-storage technology due to potential improvements in energy density and safety compared to current conventional technologies. Due to their high ionic conductivity and potential scalability through traditional slurry processing sulfide electrolytes are a very promising candidate to replace traditional liquid electrolytes and enable all-solid-state batteries. Yet, there remain many issues with regards to high interfacial resistance at the solid-solid electrode-electrolyte interfaces. A combination of chemo-mechanical, electrochemical, and chemical processes govern charge transfer at both the cathodic and anodic interfaces. This review will present and summarize recent strategies used to limit the interfacial resistance at both the cathodic and anodic interfaces with regards to sulfide-based all-solid-state batteries.